Summary of 2002 Ridge and Indian River-South Florida Citrus Caretaker Surveys - Ronald P. Muraro (EDIS)
This is EDIS document FE 349, a publication of the Department of Food and Resource Economics, Florida Cooperative Extension Service, Institute of Food and Agricultural Sciences, University of Florida, Gainesville, FL. Published March 2003.